2021
DOI: 10.3389/fphar.2021.764331
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine: A Review of Its Antitumor Potential and Mechanisms

Abstract: Cancer remains a major public health threat. The mitigation of the associated morbidity and mortality remains a major research focus. From a molecular biological perspective, cancer is defined as uncontrolled cell division and abnormal cell growth caused by various gene mutations. Therefore, there remains an urgent need to develop safe and effective antitumor drugs. The antitumor effect of plant extracts, which are characterized by relatively low toxicity and adverse effect, has attracted significant attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 138 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…TRAF6/c-JUN/NF-κB signaling pathway, 36 enhances antitumor effects, 37 and has also demonstrated its ability to reverse breast cancer by regulating pgp-mediated expression of multidrug resistance in breast cancer cells. 38 In this study, we found that chalcone hybridized with TMP inhibited the growth of A549 cells, induced apoptosis, and showed little cytotoxicity to normal cell lines BEAS-2B.…”
mentioning
confidence: 64%
“…TRAF6/c-JUN/NF-κB signaling pathway, 36 enhances antitumor effects, 37 and has also demonstrated its ability to reverse breast cancer by regulating pgp-mediated expression of multidrug resistance in breast cancer cells. 38 In this study, we found that chalcone hybridized with TMP inhibited the growth of A549 cells, induced apoptosis, and showed little cytotoxicity to normal cell lines BEAS-2B.…”
mentioning
confidence: 64%
“…Tetramethylpyrazine (TMP) is one of the key active components found in traditional Chinese medicine Chuanxiong, which possesses various physiological functions, such as antioxidant, anti-inflammatory, anti-apoptotic, regulation of angiogenesis, and neuroprotective properties (13,14). Studies have shown that TMP can reduce the content of intracellular P-GP, thus reversing the multidrug resistance mediated by P-GP, while also increasing the…”
Section: Introductionmentioning
confidence: 99%